2024
DOI: 10.1021/jacs.3c13604
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Chalcogen Bonding Donor: Strongly Polarized Oxygen of Water

Qinpeng Zhang,
Ke Luo,
Wei Zhou
et al.

Abstract: A biscyclen molecular cabin, synthesized by connecting two cyclen macrocycles with four linkages, entraps a Li + ••• H 2 O•••Li + trimer with a water molecule clamped by two Li + ions. This configuration results in strongly polarized water, characterized by a water proton resonance shift of up to 10.00 ppm. The arrangement facilitates unprecedented O-centered chalcogen bonds between the lone pairs of pyridinyl nitrogen atoms and polarized water oxygen, as confirmed by X-ray crystallography, NMR spectroscopy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The significant role of chalcogen bonding in catalysis was recently reported . Recently, He and co-workers have shown that a metal bound water molecule acts as an electron acceptor in chalcogen bonds . The influence of the metal and donor ability of diyne substituents are well-known to influence the regiochemical outcome of C–H functionalization/diyne annulation. , However, in this manuscript, we have shown for the first time how one can control regiochemical outcome of C–H functionalization/1,3-diyne annulation by choosing heteroatom containing diynes such as 26 and 27 .…”
Section: Resultsmentioning
confidence: 75%
“…The significant role of chalcogen bonding in catalysis was recently reported . Recently, He and co-workers have shown that a metal bound water molecule acts as an electron acceptor in chalcogen bonds . The influence of the metal and donor ability of diyne substituents are well-known to influence the regiochemical outcome of C–H functionalization/diyne annulation. , However, in this manuscript, we have shown for the first time how one can control regiochemical outcome of C–H functionalization/1,3-diyne annulation by choosing heteroatom containing diynes such as 26 and 27 .…”
Section: Resultsmentioning
confidence: 75%